MCSA 70-742 cert guide : identity with Windows Server 2016 - Finkel, Benjamin (Cert guide., 2017)
"The study guide helps you master all the topics on the MCSA 70-742 exam for Windows Server 2016, including:installing and configuring Active Directory Domain Services, including domain controllers, users, computers, groups, and OUs; managing and maintaining Active Directory Domain Services, including configuration of service authentication and account policies, and challenges of complex enterprise environments; creating and managing Group Policy: objects, processing, setting, and preferences; implementing Active Directory Certification Services: installation, configuration, and management; implementing Identity Federation and Access Solutions, including Web Application Proxy and Rights Management Services."--Back cover